PSYCHOTHERAPEUTIC INTERVENTION AND EDUCATIONAL IN FATHERS AND MOTHERS WITH CHILDREN IN ELEMENTARY EDUCATION - Mendoza-Nápoles, Christian Alberto; Maldonado Santos, Elsa Beatriz; Montañez Alvarado, Priscila (Revista Electrónica de Psicología Iztacala, 2020)
A quasi-experiment was carried out with pre test and post test, with the objective of intervening in the parenting provided by the parents to their sons and daughters, through rational emotive psychotherapy and psychoeducation; the working variables of parental stress, parental anxiety, parenting style, which influence the aggressiveness and anxiety of minors. The sample was taken from three elementary schools in Ciudad Juárez, Chihuahua. Mexico. A statistically significant change of small effect was found in the anxiety of the parents of the experimental group. Likewise, statistically significant changes were found in the post test in the control group of the minors in the variables of authority of the mother, the perceived acceptance of the father by the minors, and the orientation to the perceived achievement of the father by the children. The results are discussed in terms of complementarities and discrepancies with the theory.